2016
DOI: 10.1089/neu.2015.3919
|View full text |Cite
|
Sign up to set email alerts
|

Thinner Cortex in Collegiate Football Players With, but not Without, a Self-Reported History of Concussion

Abstract: Emerging evidence suggests that a history of sports-related concussions can lead to long-term neuroanatomical changes. The extent to which similar changes are present in young athletes is undetermined at this time. Here, we tested the hypothesis that collegiate football athletes with (n = 25) and without (n = 24) a self-reported history of concussion would have cortical thickness differences and altered white matter integrity relative to healthy controls (n = 27) in frontotemporal regions that appear particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 57 publications
3
38
0
1
Order By: Relevance
“…20 There was no significant relationship between KYN metabolites and cortical thickness in either football athlete groups ( p's > 0.05). The ratio of KYNA/3HK, however, was correlated with cortical thickness in the left ventromedial PFC in HC (q 21 = 0.48, r = 0.39, p = 0.026; Fig.…”
Section: Exploratory Correlation Analysesmentioning
confidence: 79%
See 2 more Smart Citations
“…20 There was no significant relationship between KYN metabolites and cortical thickness in either football athlete groups ( p's > 0.05). The ratio of KYNA/3HK, however, was correlated with cortical thickness in the left ventromedial PFC in HC (q 21 = 0.48, r = 0.39, p = 0.026; Fig.…”
Section: Exploratory Correlation Analysesmentioning
confidence: 79%
“…20 A positive correlation between left ventromedial PFC thickness and KYNA/3HK was observed, however, in HC, and left hippocampal volume was significantly correlated with cortical thickness in both regions in HC but not in either football athlete group. The positive relationship between KYNA/3HK and left ventromedial PFC in HC is consistent with the hypothesis that KYNA/3HK is a neuroprotective measure given the respective actions of KYNA and 3HK in the CNS.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…In 2012, a systematic review of the DTI and concussion literature [65] reported on eight studies and raised concern in the literature at the time that there was so much variability in the methodology bringing together the findings of the diverse range of work and attempting to interpret the results was challenging. A more recent DTI and concussion systematic review [49] suggested that the most consistent findings were decreased mean diffusivity and/or an increase in fractional anisotropy in white matter within 6 months post-concussion [66][67][68][69][70], but these findings are not universal (i.e., the opposite patterns have also been reported in other studies) [56,62,71]. In addition, reduced radial diffusivity has been reported [68,[72][73][74], but increase and decrease in axial diffusivity have been described [68,69].…”
Section: Neuroimagingmentioning
confidence: 92%
“…Recent studies have used traditional imaging techniques to identify thinning of the cerebral cortex in collegiate American football athletes with a documented history of concussion compared to football players without a noted history of concussion as well as non-athletes [21]. A recent retrospective study looked into the prevalence of cavum septum pellucidum (CSP) in retired professional American football athletes who presented to a memory clinic and identified a significantly higher prevalence of CSP in football players compared to controls [22].…”
Section: Imaging/vascularmentioning
confidence: 99%